2019
DOI: 10.3390/atmos11010013
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Different Filling Materials for a Biofilter at a Broiler Fattening Facility in Terms of Ammonia and Odour Reduction

Abstract: A two-stage exhaust air treatment system installed at a broiler fattening facility with 40,000 animals was investigated. The facility's exhaust air was treated first by use of a chemo-scrubber (stage 1) and afterwards by a vertical biofilter (stage 2). The biofilter was equipped with root wood and honeycombed paper pad layers (half/half) to enable a direct comparison of both filter materials' suitability. Odour samples were taken on site and afterwards analysed at an olfactometry laboratory. Ammonia concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Several studies have shown that the use of exhaust air treatment systems (EATS) on mechanically ventilated livestock buildings for pigs and poultry allows a reduction in PM, NH 3 , and/or odour emissions (end-of-pipe reduction technique). In practise, different plant systems are applied, such as biofilter 8 – 12 , trickle-bed reactor/air scrubber 13 – 15 , acid scrubber 14 , 16 , multiple stage techniques 17 – 21 as well as dry filter for separation of PM 22 , 23 . A widespread overview of the different EATSs (functional principle, design, specification for dimensioning, removal efficiency, general requirements) is given by 5 , 24 – 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the use of exhaust air treatment systems (EATS) on mechanically ventilated livestock buildings for pigs and poultry allows a reduction in PM, NH 3 , and/or odour emissions (end-of-pipe reduction technique). In practise, different plant systems are applied, such as biofilter 8 – 12 , trickle-bed reactor/air scrubber 13 – 15 , acid scrubber 14 , 16 , multiple stage techniques 17 – 21 as well as dry filter for separation of PM 22 , 23 . A widespread overview of the different EATSs (functional principle, design, specification for dimensioning, removal efficiency, general requirements) is given by 5 , 24 – 26 .…”
Section: Introductionmentioning
confidence: 99%
“…A 100 ml glass chamber was filled with crushed biochar and dried for eight hours at 80 °C in a drying cabinet to determine the density. Subsequently, the chamber was shaken briefly to compact the dried samples and fill all the available spaces in the chamber (Strohmaier et al, 2019). Ultimately, division of each sample's mass (kg) to that sample's volume (m 3 ) will present as its bulk density value.…”
Section: Bulk Densitymentioning
confidence: 99%
“…Filters are used to reduce the emissions of exhaust gases by physical, biological, and chemical processes. The outlet air filtration systems usually include air scrubbers, biofilters, and dry filters [96][97][98].…”
Section: Classificationmentioning
confidence: 99%
“…Given that particles are carriers of bacteria, dry filters also have a certain filtration effect on fungi, for which a filtration efficiency of 20% is attainable [96]. However, dry filters negligibly affect the NH 3 concentration, and thus, do little to alter the NH 3 emissions from animal housing [97]. Integrating NH 3 reduction techniques in the dry filter method is very difficult, although it should be possible to integrate a simple wet scrubber to remove NH 3 into the dry filter, potentially improving the overall dust and NH 3 removal efficiencies [97].…”
Section: Performancementioning
confidence: 99%